Proses Legalisasi dan Hambatan Dalam Pengurusan Tanah Warisan Tanpa Sertifikat - Justicia Ardha, Dea; Hasmiati, Rahmatullah Ayu Hasmiati; Jafar, Abdul; -, Syamsul (CV. Doki Course and Training, 2023)
Land is a valuable asset that has historical value. To avoid legal complications down the line, it is crucial to ensure that the land is officially titled and registered in the owner's name. Obtaining ownership rights for land can take place either through the inheritance process or by obtaining land certification. However, if the inherited land does not have a certificate, it can cause problems in the division of the inherited property. Legalisation of uncertificated inherited land is important to provide legal certainty for the heirs. The research in this study employs a normative juridical approach, which involves legal research grounded in statutory regulations. The process of legalising inherited land without a certificate can be done by first arranging the Death Letter / Death Certificate of the Heir, then after obtaining the letter, a Certificate of heirs can be submitted first along with a Certificate of ownership from the Lurah / The Head of the Village along with a certificate indicating that the land has not undergone certification, then a new application for registration of the land can be submitted. Land registration aims to ensure a person's right to land, prevent border disputes, and determine the amount of tax. Through registration, an individual can secure clarity regarding their land rights, encompassing ownership rights, business use rights, building use rights, and various others. Many lands are not yet certified due to sub-optimal land registration and people's inability to apply for certificates. Factors that hinder the community include high costs, lack of understanding of registration procedures, and the process is complicated and complex.